Tantangan Awal Perubahan Kehidupan (Penyangkalan Diri) - Grasela Sinta; Hurmanisa Hurmanisa; Sepri Sepri; Dr. Sarmauli (Jurnal Magistra, 2024)
The process of repentance and life change does not happen overnight, but rather through a long journey full of challenges. Such challenges include fear and doubt, discomfort from old habits, rejection and criticism from others, temptations that can lead to setbacks, and the need for patience and perseverance. To overcome this challenge, believers are encouraged to always pray and ask God for forgiveness, read the Bible and listen to God, and put to death the lust of the flesh by taking up the cross, which means facing suffering and trials faithfully. Through these actions, a person's faith can grow strongly, enabling them to better face temptations and challenges. Ultimately, strong commitment and self-denial are the keys to living a new life in accordance with God's will.